91.3k views
5 votes
Consider functions fg, and h below. 12 + 25 + 3 8 6 2 6 2 6 FB 2 6 8 Х 0 1 2. 3 h(x) -7 -4 -1 2 5

1 Answer

2 votes

We have the functions,


\begin{gathered} f(x)=x^2+2x+3 \\ \text{the rate of change of f(x) over (0,2 ) is } \\ rate-of-change=(f(2)-f(0))/(2-0) \\ f(2)=2^2+2(2)+3=11 \\ f(0)=0^2+0+3=3 \\ so,\text{ average rate of change=}(11-3)/(2)=4 \end{gathered}

We move over to g(x), g(x) is an exponential function;


\begin{gathered} \text{From the graph,} \\ g(2)=7\text{ and g(0)=4} \\ so\text{ the average rate of change of g(x) over the interval (0,2) is} \\ (g(2)-g(0))/(2-0) \\ =(7-4)/(2) \\ =(3)/(2)=1.5 \end{gathered}

We move over to h(x),


\begin{gathered} \text{From the table, h(0)=-4, h(2)=2} \\ \text{the rate of change of h(x) over the interval (0,2) is;} \\ (2-(-4))/(2-0)=(6)/(2)=3 \end{gathered}

If we rank the rates of change of the function , we see that,


4>3>1.5

So, the rates of change from least to greatest is;

g,h,f.

Option B

User RunningAdithya
by
5.4k points